Bonding Performance of Universal Adhesives Applied to Nano-Hydroxyapatite Desensitized Dentin Using Etch-and-Rinse or Self-Etch Mode - Yuchen Meng (Materials, 2021)
The study assessed the bonding performance of three universal adhesives on desensitized dentin with etch-and-rinse mode or self-etch mode after nano-hydroxyapatite (nHAp)-based desensitizers application. Simulated sensitive dentin specimens were prepared and separated into four groups: no treatment as the negative control, groups desensitized by Biorepair toothpaste, Dontodent toothpaste, or nHAp paste. Three universal adhesives of All-Bond Universal, Single Bond Universal, and Clearfil Universal Bond with etch-and-rinse or self-etch mode were bonded to the desensitized dentin specimens separately, followed by resin composite build-ups. Micro-tensile bond strength was measured using a micro-tensile tester. The wettability of desensitized dentin was evaluated by the contact angle of the adhesives. Resin infiltration was observed by confocal laser scanning microscopy. Dentin tubular occlusion and nanoleakage were observed by scanning electron microscope. The results showed that the etch-and-rinse or self-etch mode of each adhesive showed similar bond strength when bonding to nHAp-based desensitized dentin. The dentin surface was partially covered by desensitizers after desensitization. Compared with the self-etch mode, stronger demineralization and more reopened dentin tubules were observed in the etch-and-rinse mode after acid etching; longer resin tags and more nanoleakage in the resin–dentin interface were observed when using the etch-and-rinse mode. When bonding to nHAp-based desensitized dentin with universal adhesives, no significant difference in bond strength was found between self-etch mode or etch-and-rinse mode; while the latter produced more nanoleakage in the resin–dentin interfaces.